Preliminary Results of a Study of the Relationship Between the Monthly Mean Sum of Atmospheric Precipitation and Landslide Cases in Georgia - Amiranashvili, Avtandi A.; L. Chelidze, Tamaz; Dalakishvili, Lasha I.; T. Svanadze, Davit; N. Tsamalashvili, Tamar; A. Tvauri, Ganadi (Journals of Georgian Geophysical Society, 2020)
Preliminary results of the study of the influence of the mean monthly sum of atmospheric precipitation on landslides in Georgia are presented. In particular, it was found that with an increase in the monthly amount of atmospheric precipitation, there is a linear tendency for an increase in the number of landslides.